2018
DOI: 10.1177/1071100718768509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Significance of Mortise Instability in Supination External Rotation Fibula Fractures: A Review Article

Abstract: Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
1
10
0
1
Order By: Relevance
“…During axial loading, even in the presence of a partial tear, the talus remains anatomically reduced within normal limits of MCS on WB radiographs. 13 This lends supports to the theory that ankle stability can be thought of as a spectrum rather than simply stable or unstable, and perhaps further validation with higher levels of evidence would be required. Preliminary reports of WB computed tomography have recently been published with promising results.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…During axial loading, even in the presence of a partial tear, the talus remains anatomically reduced within normal limits of MCS on WB radiographs. 13 This lends supports to the theory that ankle stability can be thought of as a spectrum rather than simply stable or unstable, and perhaps further validation with higher levels of evidence would be required. Preliminary reports of WB computed tomography have recently been published with promising results.…”
Section: Discussionsupporting
confidence: 58%
“…2,3 The patterns of instability may not be apparent on standard radiographs. 2,3,13,29 Fractures with suspected deltoid ligament injury require careful evaluation and treatment, as inability to maintain anatomical alignment of the ankle has clinical and biomechanical implications with potential for poor outcomes. 6,24 Stable SER fractures can effectively be treated nonoperatively with functional bracing and early mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have demonstrated the negative effects of malalignment on the contact area, contact pressures, and the development of arthrosis, short-term assessments are unlikely to predict long-term functional outcomes. 28,29) To the best of our knowledge, this is the first study that compares US findings to those of arthroscopy for patients with isolated lateral malleolar fractures. Our results confirmed that all patients had complete or partial deltoid ligament rupture surgically.…”
Section: Discussionmentioning
confidence: 97%
“…Investigators continue to examine the diagnosis and treatment of bimalleolar-equivalent ankle fractures. A recent review by Kwon et al 11 illustrated consensus that accurate assessment of the integrity of the deltoid ligament is important for guiding treatment and optimizing outcomes. There are several commonly utilized techniques to determine ankle instability for the apparent, isolated lateral malleolar fracture.…”
Section: Discussionmentioning
confidence: 99%